Park-based physical activity interventions for persons with disabilities: A mixed-methods systematic review. Issue 1 (January 2019) - Saitta, Miles; Devan, Hemakumar; Boland, Pauline; Perry, Meredith A.
Abstract: Background: Park-based physical activity (PA) interventions improve health in the general population, but it is unknown if the evidence can be translated to persons with disabilities. Objectives: To conduct a mixed-methods systematic synthesis of the evidence for park-based physical activity interventions for persons with disabilities and secondarily, to consider the health benefits across the lifespan (children and adolescents, young, middle, and older adults). Methods: All major electronic databases were searched from inception until 30 th November 2016. Studies were eligible if the PA intervention was conducted in an urban park environment with people reporting a disability (e.g. physical, psychological and developmental impairments) and health outcomes were evaluated with biopsychosocial measures. Methodological quality was assessed using Crowes Critical Appraisal Tool (CCAT) and key findings extracted. Results: Six quantitative and four qualitative papers, comprising of 446 participants (age range seven to ninety-one years), were included for qualitative synthesis; five in children/adolescents, none in adults, and five in older adults. There was limited, low level, preliminary evidence for short-term improvements in physical, psychological, and social health outcomes in children and older adults with disabilities as well as improvements in disability-related impairments. When accessible, parks fostered societal inclusion. Conclusions: Health benefits from park use in persons with disabilities were identified. Parks may provide an alternative environment for rehabilitation and management of disabilities. Further randomized controlled trials evaluating the long-term effectiveness of park-based interventions is necessary to corroborate our findings. Legislative commitment ensuring urban parks are accessible may mitigate some health disparities in persons with disabilities.